Sistemas de previsão de ocorrência de requeima em clones de batata suscetíveis e resistentes - Bosco, Leosane Cristina (2008)
The occurrence of late blight (Phytophthora infestans (Mont) de Bary) in potato crops is responsible for a large amount of fungicides every season. The use of systems for forecasting and late blight resistant cultivars are important tools to reduce the amount of fungicides and thereby reduce production costs and environmental pollution. The objective of this study was to evaluate forecast systems for late blight occurrence in Macaca, SMIJ461-1, and SMINIA793101-3 potato clones in Santa Maria, RS, Brazil. The experiments were carried out at the experimental area of the Fitotecnia Department during Spring 2006 and Autumn 2007. Meteorological data were collected at the centre of the experimental area with an automatic station and with psicrometric pairs installed at different heights, connected to a datalogger. Thirteen treatments were used arranged in a completely randomized design, with four replications. Treatments were differentiated by using accumulated values of severity, which were calculated by Blitecast and Prophy forecasting systems, and the clones characterized as susceptible (Macaca) and resistant (SMIJ461-1 and SMINIA793101-3) to late blight. The values of severity accumulated had the purpose of indicating the time of fungicide application for late blight control. The use of forecast systems for late blight in potatoes of a susceptible genotype, Macaca, reduced the number of fungicides applications without affecting the productivity of the crop, using the Prophy forecasting system, with accumulation of 20 or 25 severity values. In the Prophy forecasting system with 15 accumulated values of severity, there was a better control of late blight than in the weekly scheme, although, the increase in productivity was not significant. The Blitecast forecasting system was not effective to predict infection to control late blight and, therefore, it must be adjusted, particularly regarding height measurement for relative humidity and air temperature. For resistant clones, the use of forecasting systems for late blight in potatoes has no effect on the disease occurrence and productivity of the crop.